Two-dimensional metal-organic framework-derived selenium-doped cobalt Sulfide@Graphene nanofoam for oxygen electrocatalysis. (30th June 2021) - Xie, Chuyi; Wang, Qijun; Xiao, Chen; Yang, Lite; Lan, Minqiu; Yang, Shengxiong; Xiao, Junwu; Xiao, Fei; Wang, Shuai
Abstract: Herein, we report an in-situ recrystallization strategy for preparing two-dimensional metal-organic framework uniformly anchored on graphene sheets, and further design selenium-doped cobalt sulfide@graphene nanofoam via the anion doping as a highly efficient bifunctional oxygen catalyst. Doping selenium atoms into cobalt sulfide not only is favourable for accelerating the transition from ∗OH to ∗O via increasing the electron density around cobalt centers, but also induces the formation of effective metal-oxygen and selenite/selenate species, resulting in significantly increasing the oxygen evolution reaction activity without the obvious deterioration of the oxygen reduction reaction activity. Moreover, graphene nanofoam supports with hierarchical porosity and high crystallinity provide large ion-accessible surface area for sufficiently exposing active sites to the electrolyte and prevents the deactivation of active sites via the formation of a 3–5 layered graphene at the surface as a protective layer. Hence, a superior catalytic performance is achieved with a comparable mass activity to Pt/C catalyst and an overpotential of 347 mV at 10 mA cm −2 for the oxygen evolution reaction. This work gives an insight into the design of efficient and robust first-row transition-metal electrocatalysts via structural engineering and anionic doping. Graphical abstract: Image 1 Highlights: An in-situ recrystallization method is reported for growing two-dimensional MOF on graphene nanosheet. Nanofoam structure is more favourable for exposing active species to the electrolyte compared to the nanosheet. Selenium atoms doped into cobalt sulfide increase the OER intrinsic activity by 3.3 times.